Spectrum Auction Designs and Revenue Variations - Madden, Gary; Saglam, I.; Hussain, I. (Routledge, 2015)
This study examines a sample of 93 national 3G spectrum auctions for the period 2000–2011 to identify the sources of substantial revenue variations. An implied reduced-form econometric model that recognises the censored nature of the sample relates per capita winning bid (per Mhz, per million populations) values to regulator-determined auction design characteristics, auction competitiveness, mobile wireless market conditions and spectrum package attributes identified from tender documents. The analysis reveals that among other factors, all auction design characteristics independently impact on realized 3G spectrum auction revenues